Impact of mutations in immunodominant regions of SARS-CoV-2 variants on recognition by CD8+ T cell: An in silico analysis - Greice Carolina Santos da Silva; Victoria Cruz Paraná; Filipe Ferreira de Almeida Rego; Mariana Maciel Portela; Mariana Barros Queiroz; Raimundo Coutinho Junior; Carlos Gustavo Regis da Silva; Luana Leandro Gois; Maria Fernanda Rios Grassi (Journal of Infection and Public Health)
Background: This study aimed to investigate whether mutations in the immunodominant regions of the S, M, and N proteins of the Gamma, Delta, and Omicron SARS-CoV-2 variants that circulated in Brazil affect the recognition of viral antigens by Brazilian HLA-I-restricted CD8+ T cell epitopes, using an in silico approach. Methods: Sequences of the Gamma (n = 36,174), Delta (n = 35,129), and Omicron (n = 336) variants were retrieved using GISAID. Consensus sequences were generated using Geneious software with NC045512 as a reference. Epitopes for the S, M, and N proteins of both the original and variant sequences were predicted using NetCTLpan 1.1, NetMHCpan 4.0, and VaxiJen v2.0. The positions occupied by these epitopes, with high probability of presentation, affinity to HLA molecules, and antigenicity, were identified as potentially immunodominant regions. Results: The S protein of the reference sequence (NC045512) and its variants contained 17 immunodominant regions. Delta showed the highest conservation (94.1 %, 16), followed by Gamma (82.3 %, 14) and Omicron (70.5 %, 12). Omicron exhibited the greatest mutational variability and had regions of increased antigenicity and two novel immunodominant regions with broader human leukocyte antigen (HLA) recognition. Additionally, Omicron lost two previously identified immunodominant regions and had one region of reduced antigenicity that did not affect HLA recognition. Gamma had mutations in three regions that increased both antigenicity and HLA recognition. Delta had only one mutated region with lower antigenicity, which did not affect HLA recognition. Notably, new immunodominant regions for the M and N proteins appeared in the Omicron variant. Conclusions: Brazilian HLA-I-restricted CD8+ T cell epitopes from SARS-CoV-2 immunodominant regions are partially conserved in the Gamma, Delta, and Omicron variants circulating in Brazil, suggesting effective a cross-protective immune response that may help reduce COVID-19 severity and mortality.